Fission yeast global repressors regulate the specificity of chromatin alteration in response to distinct environmental stresses - Hirota, Kouji (Oxford University Press, 2004)
The specific induction of genes in response to distinct environmental stress is vital for all eukaryotes. To study the mechanisms that result in selective gene responses, we examined the role of the fission yeast Tup1 family repressors in chromatin regulation. We found that chromatin structure around a cAMP-responsive element (CRE)-like sequence in ade6-M26 that is bound by Atf1·Pcr1 transcriptional activation was altered in response to osmotic stress but not to heat and oxidative stresses. Such chromatin structure alteration occurred later than the Atf1 phosphorylation but correlated well with stress-induced transcriptional activation at ade6-M26. This chromatin structure alteration required components for the stress-activated protein kinase (SAPK) cascade and both subunits of the M26-binding CREB/ATF-type protein Atf1·Pcr1. Cation stress and glucose starvation selectively caused chromatin structure alteration around CRE-like sequences in cta3(+) and fbp1(+) promoters, respectively, in correlation with transcriptional activation. However, the tup11Δ tup12Δ double deletion mutants lost the selectivity of stress responses of chromatin structure and transcriptional regulation of cta3(+) and fbp1(+). These data indicate that the Tup1-like repressors regulate the chromatin structure to ensure the specificity of gene activation in response to particular stresses. Such a role for these proteins may serve as a paradigm for the regulation of stress response in higher eukaryotes.